Dynamics of Network Utilization in Internationalization What SMEs Do in Developing and Developed Countries: A Systematic Literature Review - Rahayu, Rahayu; Sudarmiatin, Sudarmiatin; Sumarsono, Hadi (International Journal of Science, Technology & Management, 2023)
The study of networks in the internationalization process of SMEs has become an interesting discussion, this condition is because each country has unique dynamics in utilizing existing networks. The results of the analysis of the 20 articles in this study show that being proactive in the network community will strengthen relationships with partners and implementing an alliance strategy will strengthen the position of SMEs in increasing competitiveness and expanding markets. This condition occurs in both developing and developed countries. The dominant factor influencing the speed of the internationalization process is social and business network relations that begin with social ties. Of the 8 articles that discuss networking in the process of internationalization in developed countries (China, Central America, and East America), it shows that the government as an institution that has an important role in the internationalization of SMEs needs to design a framework in the form of policies that encourage the acceleration of various forms of collaboration between businesses. Meanwhile, 12 articles that discuss the process of internationalization in developing countries show that for the expansion and growth of SMEs a social network structure is needed, and the role of ethnic (group) ties in internationalization.